Republic of Poland : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Poland. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that Poland's rapid growth had begun to lose steam even before the global crisis hit. Following robust and relatively well-balanced expansion, driven by an EU accession-related investment boom and rapid credit and wage growth, economic activity began to slow down in the face of capacity constraints. Executive Directors have noted that a significant deceleration in economic activity is under way, reflecting adverse spillovers through real and financial channels. They have also commended the authorities for the timely, well-focused, and measured policy response.